THE INFLUENCE OF USING LISTEN-READ-DISCUSS (LRD) STRATEGY TOWARDS STUDENTS’ READING COMPREHENSION ON REPORT TEXT OF THE ELEVENTH GRADE OF SMK SWASTA PAB 2 HELVETIA - Feby Syafitri; Enni Maisaroh (Universitas Potensi Utama, 2021)
The purpose of this research was to see evidance about improvement of the students’ reading comprehension by using LRD strategy. LRD strategy was used to solve students’ problem in comprehending text. Based on Manzo and Casale LRD strategy was a strategy that can helps the students more effective in reading process, because it was a strategy that makes the students active, motivated and comprehend text. This research was experimental research in quantitative approach. The sample of this research were eleventh grade students of Smk Swasta PAB 2 Helvetia, which consisted of 64 students divided into two classes, the experimental group and the control group as sample consisting of 32 students in each class. The experimental group was taught using LRD strategy, while the control group was taught using conventional method. The data was obtained using pre-test and post-test. Pre-test was given to both groups before treatment and post-test was given after treatment. Then, the instrument used to collect data was multiple choices in the form of English text. To analyze the data, researcher used t-test. The significance value calculated 0.000 is smaller than 0.05 (P-value = 0.000 < 0.05). Based on the results of calculations, tobserved 4.175 and ttable value (0.05) 1.699. We know that tcount is higher than ttable (tcount > ttable) = (4,411>1,686). This means, that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. It can be concluded that LRD strategy significantly influences students' reading comprehension in second grade students at SMK Swasta PAB 2 Helvetia. The benefit of this research was LRD strategy help students’ to be active and more undestand in learning English. It is hope that, students can improve their ability in reading text.